Effect of local anesthetics on the organization and dynamics in membranes of varying phase: A fluorescence approach. (June 2016) - Shrivastava, Sandeep; Dutta, Diya; Chattopadhyay, Amitabha
Highlights: PEtOH induces disorder in membranes of varying phases. The extent of membrane disorder induced by PEtOH varies in a phase-specific manner. Higher PEtOH concentrations induce phase change in gel phase membranes. These results assume significance in the context of role of anesthetic in membrane function. Abstract: The molecular mechanism underlying the action of local anesthetics remains elusive. Phenylethanol (PEtOH) is an ingredient of essential oils with a rose-like odor and has been used as a local anesthetic. In this work, we explored the effect of PEtOH on organization and dynamics in membranes representing various biologically relevant phases using differentially localized fluorescent membrane probes, DPH and TMA-DPH. We show here that PEtOH induces disorder in membranes of all phases (gel/fluid/liquid-ordered). However, the extent of membrane disorder varies in a phase-specific manner. Maximum membrane disordering was observed in gel phase, followed by liquid-ordered membranes. The disordering was minimal in fluid phase membranes. Interestingly, our results show that the disordering effect of PEtOH in gel phase is sufficiently large to induce phase change at higher PEtOH concentrations. Our results are relevant in the context of natural membranes and could be useful in understanding the role of anesthetics in membrane protein function.